Role of mitochondria in the regulation of ferroptosis and disease - Fu, Cheng; Cao, Nan; Zeng, Sen; Zhu, Wenhui; Fu, Xinliang; Liu, Wenjun; Fan, Shuangqi (Frontiers in Medicine, 2023)
Ferroptosis is a distinctive form of iron-dependent cell death characterized by significant ultrastructural changes in mitochondria. Given the crucial involvement of mitochondria in various cellular processes such as reactive oxygen species production, energy metabolism, redox status, and iron metabolism, mounting evidence suggests a vital role of mitochondria in the regulation and execution of ferroptosis. Furthermore, there exists a strong correlation between ferroptosis and various diseases. In this review, we aim to summarize the mechanisms underlying the induction and defense of ferroptosis, emphasizing the influence of mitochondria on this intricate process. Additionally, we provide an overview of the role of ferroptosis in disease, particularly cancer, and elucidate the mechanisms by which drugs targeting mitochondria impact ferroptosis. By presenting a theoretical foundation and reference point, this review aims to contribute to both basic cell biology research and the investigation of clinically relevant diseases.